Sensing Sub‐Surface Strain in GaAsBi(001) Surfaces by Reflectance Anisotropy Spectroscopy. Issue 11 (4th September 2022) - Bonanni, Beatrice; Fazi, Laura; Tisbi, Elisa; Placidi, Ernesto; Arciprete, Fabrizio; Goletti, Claudio
Abstract : Reflectance anisotropy spectroscopy (RAS) is applied to study the reconstructed GaAsBi(001) surfaces at room temperature. Arsenic‐capped GaAsBi samples with 7% Bi concentration are grown by molecular beam epitaxy (MBE) in nearly matched conditions on a proper buffer layer and annealed in ultra‐high vacuum (UHV). Low energy electron diffraction (LEED) shows that, following the As decapping, a 2 × 3/1 × 3 phase (Bi‐rich) is obtained after annealing the sample at 400 °C, while subsequent annealing at 450 °C yields a deterioration of the surface order. RAS spectra measured in situ allow to definitely confirm that the characteristic Bi‐dependent anisotropy measured below 2.5 eV has not a true surface origin, although being connected to the surface: it is related to the strain of the directional bonds between Bi atoms existing at the surface and below the surface. This result has a twofold significance: it recommends that previous attributions to the surface of RAS anisotropy features in III–V semiconductors should be in some cases revisited; for the future, it shows that RAS is suitable to characterize 2D‐layered materials, and to investigate the consequences of strain in the electronic properties of low‐dimensional systems. Abstract : Reflectance anisotropy spectroscopy (RAS) is suitable to investigate the effect of strain on the electronic properties of 2D‐layered materials. It enables to follow in real time the optical/electronic properties during the growth of GaAsBi in molecular beam epitaxy (MBE) and metal–organic vapor pressure epitaxy (MOVPE).